Resolution and Contrast Sensitivity of the Radiograph after Irradiation together with Vinyl Sticker and Waistband - Nurul Fadhlina Ismail; Humairah Hakimah Mohamad Rani (Asian Journal of Medicine & Health Sciences, 2022)
Background: Typically, patients wear their underwear during X-ray examination, but it may be visible on the X-ray images thus affect the image quality. Therefore, the aim of this study is to investigate the effects of vinyl stickers and waistband on the contrast and resolution of radiographs. Methods: TOR CDR (Leeds Test Object, UK) was irradiated with X-ray photons at 70kVp, 20mAs using a computerised radiography system, either directly or over the thickness of the sticker or waistband. The contrast and resolution of the X-ray image were calculated based on the manufacturer’s guidelines. Results: As the thickness of the sticker or waistband increased, the sensitivity to high and low contrast increased significantly and the resolution decreased (sticker: high contrast, p value =0.01; low contrast, p value =0.04; resolution, p value =0.22, wristband: high contrast, p value =0.01; low contrast, p value =0.02; resolution, p value =0.08)). There was a statistically significant effect on image quality after the TOR CDR was overlaid with the sticker or wristband (p-value <0.001). Conclusion: As the thickness of the vinyl stickers and waistband increases, image contrast and resolution deteriorate. Therefore, it is important that patients remove their underwear or other clothing with vinyl stickers or waistbands for the appropriate X-ray examination.